Black Theology as Mass Movement - Howard, C. author. aut Link
XIV, 187 p.
Keywords: Black Theology as Mass Movemen t is a call to current and future theologians to stretch the boundaries of Black Liberation Theology from what has become primarily an academic subfield into a full fledge liberation movement beyond the walls of the academy.